Natural Killer Cell and Large Granular Lymphocyte Deficiency in the Gut of Children with Inflammatory Bowel Disease - F Hadziselimovic; LR Emmons; U Schaub (Canadian Journal of Gastroenterology)
The occurrence of natural killer cells and large granular lymphocytes (LGL) within the epithelium of colonic mucosa in children with inflammatory bowel disease (IBD) was compared to normal controls. Their numbers and localization within the epithelium from various regions of the colon were analyzed with immunohistochemical techniques using fluorescent, light and electron microscopy. The average number of natural killer cells and LGL in normal controls was 3.0±1.l per mn2. In contrast, there were no natural killer cells in the gut epithelium of children with IBD, irrespective of disease activity, whether the biopsy specimens were obtained from involved or uninvolved inflammatory regions of the gut, or the treatment status of the patients. However, the number of natural killer cells was normal in patients in remission with left-sided colitis. The lack of natural killer cells and LGL in the gut epithelium in children with IBD may be indicative of a possible genetic predisposition. The authors also present a new therapeutic strategy consisting of low dose interferon-alpha-2a that is efficacious in ameliorating ulcerative col iris and Crohn's disease and concomitantly increasing the number of natural killer cells and LGL in the gut.